Prevalence and Determinants of Long-Term Utilization of Antidepressant Drugs: A Retrospective Cohort Study - Lunghi C (Dove Medical Press, 2020)
Carlotta Lunghi,1– 3 Ippazio Cosimo Antonazzo,2 Sofia Burato,2 Emanuel Raschi,2 Violetta Zoffoli,2 Emanuele Forcesi,2 Elisa Sangiorgi,4 Marco Menchetti,5 Pasquale Roberge,3,6 Elisabetta Poluzzi2 1Department of Health Sciences, Université Du Québec À Rimouski, Lévis, Québec, Canada; 2Department of Medical and Surgical Sciences, Pharmacology Unit, Alma Mater Studiorum, University of Bologna, Bologna, Italy; 3Groupe De Recherche PRIMUS, Centre De Recherche Du CHUS, Université De Sherbrooke, Sherbrooke, Canada; 4Drug Policy Service, Emilia Romagna Region Health Authority, Bologna, Italy; 5Department of Biomedical and Neuromotor Sciences, Alma Mater Studiorum, University of Bologna, Bologna, Italy; 6Faculty of Medicine and Health Sciences, Université De Sherbrooke, Sherbrooke, Québec, CanadaCorrespondence: Carlotta LunghiDepartment of Health Sciences, Université Du Québec À Rimouski, 1595 Boulevard Alphonse Desjardins, Lévis, Québec G6V 0A6, CanadaTel +1 418-833-8800 Ext. 3275Email Carlotta_Lunghi@uqar.caPurpose: Antidepressant consumption has risen in recent years, driven by longer treatment duration. The objective of this study was to measure the prevalence of antidepressant long-term and chronic use in the Bologna area, Italy, and to identify their main determinants.Materials and Methods: We conducted a retrospective claims-based cohort study by using the Bologna Local Health Authority data. A cohort of 18,307 incident users of antidepressant drugs in 2013 was selected, and subjects were followed for three years. A long-term utilization was defined as having at least one prescription claimed during each year of follow-up, while chronic utilization was defined as claiming at least 180 defined daily doses per year. Factors associated with chronic and long-term use were identified by univariate and multivariate logistic regressions.Results: In our cohort, 5448 (29.8%) and 1817 (9.9%) subjects were dispensed antidepressants for a long-term course and in a chronically way, respectively. Older age, antidepressant polytherapy, polypharmacy, and being prescribed the first antidepressant by a hospital physician were all factors independently associated with chronic and long-term prescriptions of antidepressant drugs. Results were reported separately for men and women.Conclusion: Antidepressant long-term and chronic prescriptions are common in the Bologna area. Because longer treatment should be clinically motivated, these results strongly prompt the need to evaluate the actual relevance, as they may indicate potentially inappropriate prescription patterns.Keywords: antidepressants, depression, anxiety, anxiety disorders, primary care, pharmacotherapy, adherence, epidemiology, pharmacoepidemiology, treatment